Astragaloside IV protects rat retinal capillary endothelial cells against high glucose-induced oxidative injury - Qiao Y; Fan C; Tang M (Dove Medical Press, 2017)
Yuan Qiao, Chun-Lan Fan, Min-Ke Tang School of Chinese Materia Medica, Beijing University of Chinese Medicine, Chaoyang District, Beijing, People’s Republic of China Aim: Diabetic retinopathy is a microvascular complication of diabetes that leads to blindness. Hyperglycemia causes oxidative stress, which is an important cause in the pathogenesis of microangiopathy. The aim of this study was to investigate the potential protective effects of astragaloside IV (AS-IV) in retinal capillary endothelial cells (RCECs) incubated with high glucose conditions. Methods and results: Based on rat RCECs cultured with high glucose (30 mM) in vitro, a significant increase in cell viability in rat RCECs incubated with both AS-IV and high glucose for 48 or 72 h by MTT assay. The increased viability was accompanied by decreased glucose transporter-1 expression using immunofluorescent assay. Meanwhile, AS-IV reduced intracellular hydrogen peroxide and superoxide, decreased mitochondrial reactive oxygen species in rat RCECs with high glucose by the fluorescent probes, and lowered malondialdehyde levels. In addition, AS-IV increased the activities of total superoxide dismutase, MnSOD, catalase, and glutathione peroxidase. The glutathione content also increased after AS-IV treatment. Furthermore, AS-IV reduced NADPH oxidase 4 expression by western blot method. Conclusion: These results suggest that the main mechanism underlying the protective effects of AS-IV in high glucose-injured RCECs may be related to its antioxidative function. Keywords: astragaloside IV, retinal capillary endothelial cells, oxidative stress, Glut1, Nox4